Supervisory-Driven Madrasah Development: Strengthening the Implementation of the Merdeka Curriculum in Indonesian Madrasah Aliyah - Evy Ramadina; Agus Zaenul Fitri; Sulistiyorini Sulistiyorini (Tarbawi: Jurnal Keilmuan Manajemen Pendidikan, 2026)
Educational supervision is commonly regarded as a major source of instructional improvement and institutional performance. However, it is largely administrative in many educational institutions and restricts its contribution to sustainable school development. The challenge is particularly acute in implementing Indonesia’s Merdeka Curriculum, which demands adaptable leadership, collaborative professional learning, and continual organizational improvement. The purpose of this research is to examine the role of educational supervision as a strategic tool for sustainable madrasa development in the context of curriculum reform. We used a qualitative phenomenological approach to understand the lived experiences of educational stakeholders at MA Al Fattahiyyah. Data collection was conducted through in-depth interviews, participant observation, and document analysis with madrasa principals, vice principals, teachers, and educational professionals. The data were analyzed using an interactive model by Miles et al. The findings show that educational supervision occurs through three interconnected dimensions: collaborative professional supervision, reflective conversation, and internal quality assurance. All these elements contribute to enhancing teachers' professional competence, organizational learning, curricula implementation, and institutional quality. Based on these findings, this study proposes the Strategic Collaborative Educational Supervision (SCES) framework, which conceptualizes educational supervision as an integrated governance system that connects instructional leadership, collaborative professional learning, organizational learning, and adaptive curriculum governance. The study contributes to the literature of educational leadership and Islamic educational management by extending the traditional supervision from administrative evaluation to a strategic competence for sustainable institutional development. The proposed framework provides practical guidance for madrasa leaders, educational supervisors, and policymakers to improve the quality of education and facilitate the effective implementation of the Merdeka Curriculum.